A clinical risk score of myocardial fibrosis predicts adverse outcomes in aortic stenosis - Calvin Chin; David Messika‐Zeitoun; Anoop Shah; Guillaume Lefèvre; S. Bailleul; Emily Yeung; Maria Koo; Saeed Mirsadraee; Tiffany Mathieu; Scott Semple; Nicholas L. Mills; Alec Vahanian; et al. (2015)
Midwall myocardial fibrosis on cardiovascular magnetic resonance (CMR) is a marker of early ventricular decompensation and adverse outcomes in aortic stenosis (AS). We aimed to develop and validate a novel clinical score using variables associated with midwall fibrosis.